Financing apprenticeships in the EU - (:unkn) unknown (Publications Office of the European Union, 2020)
"The study 'Financing apprenticeships in the EU' adds to a series of research and policy activities carried out by Cedefop to support development of apprenticeships and to inform on financing vocational education and training (VET). It presents the first systematic attempt to collect and analyse financing information on all apprenticeship schemes identified in the EU countries and the UK. The study covers 29 apprenticeship schemes in 21 EU countries and the UK. While previous research focused on specific issues, such as cost-benefit of apprenticeships from the viewpoint of employers, this study took a more comprehensive approach by looking at the overall financing arrangements for apprenticeship. It aimed at exploring the main costs of the main actors involved in apprenticeships (employers, apprentices, State, schools and other training providers), the mechanisms allowing redistribution of financial resources among them (with a focus on incentives for employers and individuals to take up apprenticeship) and the volumes of funding involved. It demonstrates the wide variety of ways in which apprenticeships are financed and proposes a typology of financing arrangements for apprenticeships. The data were collected through a literature review and national expert surveys during 2017. " (extract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 4.1 Finanzierungsquellen; I 2.2 Europa; 370; Berufsausbildung; Bildungsfinanzierung; Ausbildungskosten; Ausbildungsinvestition; Ausbildungsbereitschaft; Vereinigtes Königreich; Europäische Union